Transcranial low-frequency ultrasound-mediated thrombolysis in brain ischemia: increased risk of hemorrhage with combined ultrasound and tissue plasminogen activator : results of a phase II clinical trial - Daffertshofer, Michael; Gass, Achim; Ringleb, Peter A.; Sitzer, Matthias; Sliwka, Ulrich Artur; Els, Thomas; Sedlaczek, Oliver; Koroshetz, Walter J.; Hennerici, Michael G. (Stroke, 2005)
BACKGROUND: Clinical studies using ultrasound at diagnostic frequencies in transcranial Doppler devices provided encouraging results in enhancing thrombolysis with tissue plasminogen activator (tPA) in acute stroke. Low-frequency ultrasound does not require complex positioning procedures, penetrates through the skull better, and has been demonstrated to accelerate thrombolysis with tPA in animal experiments in wide cerebrovascular territories without hemorrhagic side effects. We therefore conducted the first multicenter clinical trial to investigate safety of tPA plus low-frequency ultrasound (300 kHz). - METHODS: Acute stroke patients within a 6-hour time window were included (National Institutes of Health Stroke Scale scores >4). Magnetic resonance imaging (MRI) was used to document vascular occlusion and to rule out cerebral hemorrhage. Patients were allocated to combination therapy alternately; the first patient received tPA only, the second patient received tPA plus ultrasound, etc. Follow-up included serial MRI directly thereafter and 24 hours later to confirm recanalization and tissue imaging. Clinical recovery was measured after treatment and 3 months later. - RESULTS: 26 patients (70.4+/-9.7 years) entered the trial (12 tPA, 14 tPA plus ultrasound). The study was prematurely stopped because 5 of 12 patients from the tPA only group but 13 of 14 patients treated with the tPA plus ultrasound showed signs of bleeding in MRI (P<0.01). Within 3 days of treatment, 5 symptomatic hemorrhages occurred within the tPA plus ultrasound group. At 3 months, neither morbidity nor treatment-related mortality or recanalization rates differed between both groups. - CONCLUSIONS: This study demonstrated bioeffects from low-frequency ultrasound that caused an increased rate of cerebral hemorrhages in patients concomitantly treated with intravenous tPA.
Gesehen am 10.05.2022